The Relationship between Preschool Children and Pets - Μπλαβάκη Ουρανία; Καλογιαννάκης Μιχαήλ (Education Sciences, 2021)
Nowadays, the important effect that animals have on the emotional, social and cognitive development of children is accepted. Our study is part of program implemented in preschool children during the school year 2019-2020 with the main goal of raising the awareness of children, parents and teachers toward pets. Our research concerns the attitudes and perceptions of preschool children, parents and teachers about pet. In our article, through the relevant bibliographic review, reference is made to the benefits that humans have from their interaction with the pet and it is presented the relationship between pets and children. The research part analyzes the attitudes and perceptions that children have towards animals and in more detail we study the influence that pets have on preschool children.